A cost-efficient method for green synthesis of novel derivatives lower-rim-connected bisresorcinarene macrocycles in large-scale by sodium p-styrenesulfonate - Azin Kharazmi; Ramin Ghorbani-Vaghei; Ardeshir Khazaei; Idris Karakaya; Rahman Karimi-Nami (Current Research in Green and Sustainable Chemistry, 2024)
A novel, uncomplicated, and cost-effective methodology has been devised for the rapid synthesis of novel lower-rim-connected bisresorcinarene macrocycles. The incorporation of sodium p-styrenesulfonate (NaSS) facilitates the generation of a diverse array of products on a large scale, achieving high yields. Notably, the utilization of NaSS obviates the need for corrosive acids, and the absence of toxic solvents renders this reaction both environmentally friendly and economically advantageous. Furthermore, the process eliminates the necessity for column chromatography in product purification. The structural characterization of the synthesized derivatives was confirmed through comprehensive analyses, including FT-IR, 1H NMR, 13C NMR, HR-Mass, and CHNO techniques.